Significance of Wastewater Treatment to Nitrous Oxide Emission - Płuciennik-Koropczuk, Ewelina; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The sewage flowing into the wastewater treatment plant through the sewer system, as well as transported by the slurry fleet, are subjected to treatment processes. These processes, carried out under both aerobic and anaerobic conditions, contribute to the emission of greenhouse gases. On the basis of available reports and previous research, the emission of nitrous oxide (N2O) from wastewater was estimated at approx. 4-5% in relation to the global amount of this gas emission from anthropogenic sources. Data obtained from the operation of full-scale WWTPs show a wide range of values of the N2O emission factors from 0.0006 to 0.045 (kgN2O-N/kgN). The article describes possible sources of nitrous oxide emission from wastewater treatment plants and presents the basic principles of its balancing.
Keywords: greenhouse gases; nitrous oxide; municipal wastewater treatment plants; gazy cieplarniane; podtlenek azotu; komunalne oczyszczalnie ścieków